Scope of Introduction to Social Sciences in Early Childhood - Musafir, Musafir; Laela, Laela; Utami, Umratul; Hidayati, Evi; Uyun, Nurul; Zulhainah, Zulhainah; Fadila, Siska Alya; Dewi, Nurmayanti; Suryani, Ayu Gading (Jurnal Ilmiah Mandala Education (JIME), 2025)
Social science learning is closely related to the interaction between humans and other humans, humans and their environment, and human behavior itself. Social science learning in early childhood has not been included separately in school learning, but social values such as cooperation, respect, sharing, helping, love of the environment in children have been introduced by a teacher through singing or direct activities. The purpose of writing this article is to determine and explain the scope of introducing social sciences to early childhood. Meanwhile, the method for writing this article uses descriptive qualitative and the data collection technique is carried out by conducting a library study or literature study. The findings in this research include the scope of introducing social sciences to early childhood, including loving the environment, collaborating, appreciating, sharing, helping, friendly attitudes, empathy, discipline, sympathy, tolerance and mutual cooperation.